Locust lane [large type] - Amidon, Stephen (Thorndike Press large print core series., 2023)
"Can anyone be trusted? On the surface, Emerson, Massachusetts, is just like any other affluent New England suburb. But when a young woman is found dead in the nicest part of town, the powerful neighbors close ranks to keep their families safe. In this searing novel, Eden Perry's death kicks off an investigation into the three teenagers who were partying with her that night, each a suspect. Hannah, a sweet girl with an unstable history. Jack, the popular kid with a mean streak. Christopher, an outsider desperate to fit in. Their parents, each with motivations of their own, only complicate the picture: they will do anything to protect their children, even at the others' expense. With a brilliantly woven, intricately crafted plot that gathers momentum on every page, this is superb storytelling told in terse prose--a dynamic read that is both intensely gripping and deeply affecting"--